Basil (Bill Metcalf) and his toll gate: Now in Union County, New Mexico, formerly in Colfax County, New Mexico 1872 - 1885. - Taylor, Morris F. frey50
A brief biography of Bill Metcalf who operated a toll gate in New Mexico in the late 1800s, located south of Bransen Colorado, and north of Folsom, New Mexcio.
#2
Keywords: New Mexico - Northeastern New Mexico and Southeastern Colorado. -- Toll gates - History. -- Pioneers - New Mexico - Biography -- Toll Gate Canyon - New Mexico